PERAN KELUARGA DALAM MEMBENTUK ASOSIASI MEREK DAN PERSEPSI KUALITAS SERTA PENGARUHNYA TERHADAP LOYALITAS MEREK - ISLAHUDDIN DAUD; REZA GHASARMAN (Program Studi Magister Manajemen FE Unsri, 2014)
This study attempts to examine how the role of the family in shaping the brand association and perceived quality and its effect on brand loyalty. In conducting the study, researchers used a descriptive conclusive research in a single cross-sectional shape. Conclusive research is used to test specific hypotheses and test the connection. The samples used were public users everyday products that are as many as 100 people in the city of Palembang respondents using convenience sampling method. The analysis used in this study is to see the influence of regression analysis between variables. Results of the study show the family plays a role in shaping the brand association and perceived quality, and brand associations and perceived quality effect on brand loyalty. While the dominant variable influencing brand loyalty is the association.